2014
DOI: 10.3389/fnins.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenines in CNS disease: regulation by inflammatory cytokines

Abstract: The kynurenine pathway (KP) metabolizes the essential amino acid tryptophan and generates a number of neuroactive metabolites collectively called the kynurenines. Segregated into at least two distinct branches, often termed the “neurotoxic” and “neuroprotective” arms of the KP, they are regulated by the two enzymes kynurenine 3-monooxygenase and kynurenine aminotransferase, respectively. Interestingly, several enzymes in the pathway are under tight control of inflammatory mediators. Recent years have seen a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
273
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(290 citation statements)
references
References 238 publications
(304 reference statements)
11
273
0
6
Order By: Relevance
“…As noted above, kynurenine pathway metabolism is tightly regulated by inflammatory mediators and multiple enzymes in the pathway are immunoresponsive (Campbell et al, 2014). The gut microbiota engages dynamically with the host across the lifespan to educate and regulate the immune system (El Aidy et al, 2015;Round and Mazmanian, 2009).…”
Section: The Immune System the Gut Microbiota And Implications For Kmentioning
confidence: 99%
“…As noted above, kynurenine pathway metabolism is tightly regulated by inflammatory mediators and multiple enzymes in the pathway are immunoresponsive (Campbell et al, 2014). The gut microbiota engages dynamically with the host across the lifespan to educate and regulate the immune system (El Aidy et al, 2015;Round and Mazmanian, 2009).…”
Section: The Immune System the Gut Microbiota And Implications For Kmentioning
confidence: 99%
“…increased secretion of pro-inflammatory cytokines plays a particularly important role in GBM development and resistance to therapy (74)(75)(76)). An important mechanism by which these cytokines cause and worsen these diseases is through of the kynurenine pathway (77)(78)(79)(80). campbell et al showed that iFNγ activates the kynurenine pathway, and TNFα, iL1β and iL6 are synergistic with iFNγ in stimulating this pathway (77).…”
Section: Pro-inflammatory Cytokines and Indoleamine 23-dioxygenasementioning
confidence: 99%
“…An important mechanism by which these cytokines cause and worsen these diseases is through of the kynurenine pathway (77)(78)(79)(80). campbell et al showed that iFNγ activates the kynurenine pathway, and TNFα, iL1β and iL6 are synergistic with iFNγ in stimulating this pathway (77). Asp et al emphasized the important role of iFNγ in stimulating this pathway in dermal fibroblasts (78).…”
Section: Pro-inflammatory Cytokines and Indoleamine 23-dioxygenasementioning
confidence: 99%
“…serotonin, dopamine) and neuronal survival (Capuron and Miller, 2011;Dantzer et al, 2008). Indeed, increased brain or cerebrospinal fluid concentrations of kynurenine and its neurotoxic metabolites have been reported in several neurodegenerative and psychiatric disorders (Campbell et al, 2014; suggesting that IDO activation may lead to both functional and structural alterations in the brain. Consistent with this statement, activation of the kynurenine pathway has been recently reported to affect human neurogenesis in the hippocampal formation (Zunszain et al, 2012), an important brain structure involved in cognitive functions and an important site for IDO production (Andre et al, 2008;Frenois et al, 2007).…”
Section: Introductionmentioning
confidence: 99%